2017
DOI: 10.1111/cdev.12950
|View full text |Cite
|
Sign up to set email alerts
|

Black Adolescent Males: Intersections Among Their Gender Role Identity and Racial Identity and Associations With Self‐Concept (Global and School)

Abstract: Intersectional approaches for understanding identity have gained momentum in the social sciences. Black adolescent males are often perceived as threatening, underachieving, and hypermasculine, which is reinforced through media outlets and psychological research that portray them as a monolith rather than a heterogeneous group with multiple intersecting identities. This cross-sectional study of 70 Black adolescent males between 14 and 18 years old simultaneously explores their race and gender identities and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Research geared toward identifying how youth develop identities along multiple axes of difference is needed in order to learn about the diversity of pathways that promote resilience. For example, as Buckley (2017) recently demonstrated, considering gender roles alongside racial identity reveals that counter-stereotypes of either males or African Americans are protective for Black male adolescents.…”
Section: Future Directions For Researchmentioning
confidence: 98%
“…Research geared toward identifying how youth develop identities along multiple axes of difference is needed in order to learn about the diversity of pathways that promote resilience. For example, as Buckley (2017) recently demonstrated, considering gender roles alongside racial identity reveals that counter-stereotypes of either males or African Americans are protective for Black male adolescents.…”
Section: Future Directions For Researchmentioning
confidence: 98%
“…In other words, Black males are acutely aware of their intersecting identities. For this reason, we surmise that understanding Black males' mathematics identity requires an intersectional, sociocultural approach to identity development that focuses on how the contexts in which these adolescents interact influence their racial identity in addition to their gender identity (Buckley, 2018;Nasir & Saxe, 2003).…”
Section: Identity Development From a Sociocultural Perspectivementioning
confidence: 99%
“…Across 11 studies, the authors highlighted the significance of gender role attitudes in predicting mental health and performance outcomes. In all but three of these studies (Buckley, 2017; Palapattu et al, 2006; Wester et al, 2006), researchers focused on African American women and girls. The most commonly explored mental health correlates of gender role attitudes were depression (including suicidality), anxiety, stress, and self-esteem.…”
Section: Resultsmentioning
confidence: 99%
“…Among African American men, gender role conflict was directly associated with mental distress (Wester et al, 2006). For African American adolescent boys, equal endorsement of masculine and feminine traits, alongside positive regard for one’s race, were associated with enhanced self-concept (Buckley, 2017). There was only one study with results that suggested there was no relationship between gender role attitudes and mental health outcomes (Pyant & Yanico, 1991).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation